EFFORTS TO INCREASE LEARNING RESULTS OF CLASS VIII SMP IT FITHRAH INSANI ON LEARNING SYSTEM OF LINEAR TWO VARIABLE EQUIPMENT USING DIRECT INSTRUCTION MODEL WITH MEDIA POWERPOINT - Hendra Gunawan; Elis Siti Komara; Dindin Syarif (Journal Of Educational Experts (JEE), 2018)
This type of research is a classroom action research. The purpose of this study is to create a more effective teaching design on Linear Two Variable (SPLDV) System Variables (SPLDV) with one Direct Instruction lever model or direct spinning with powerpoint media in an effort to improve student learning outcomes. Abstract mathematical material requires a technique in the delivery to the students so that the material can be accepted and well understood by learners, especially on SPLDV material that contains steps of long and repetitive workmanship. The need to apply a model that can help participants in planning, monitoring and evaluating their thinking processes. In this case the need to apply a model of learning. This classroom action research is conducted in three cycles. Through this research, after application of Direct Instruction model or direct learning with powerpoint media on learning of Two-Variable Linear Equation System (SPLDV), resulted in increasing student activity in every cycle. Learners become more accustomed to planning, monitoring, and evaluating their thinking processes and accustomed to working on SPLDV questions. So also with the increasing student learning outcomes, in every cycle of the ability to work on their math problems both as a whole and every indicator continue to increase. And the action is stopped in cycle III because all the success criteria targeted has been achieved.